Cultural competence: a living theory of personal transformation within the context of higher education - Van Jaarsveldt, Deirdre Elizabeth (University of the Free State, 2011)
This living theory was developed in response to indisputable evidence that racism and other forms of discrimination are still being experienced at South African universities. As a white female educator, it was important to investigate my practices to ensure that I am sensitive to the needs of a diverse student body. Committed to a process of personal transformation, I engaged in living action research to find answers to the question: "How do I transform my practices to be more inclusive, appropriate and effective in relating to a diverse body of people within the context of higher education?" In order to gain a better understanding of inter-group relationships, I conducted a comprehensive concept analysis by engaging in a review of literature from a multiplicity of perspectives. Ethnocentrism, in its various forms of expression, was found to be the main stumbling block in intercultural relationships and therefore I engaged in an enquiry to find ways of overcoming ethnocentrism. Cultural competence, a transformative process, which involves continuously striving towards relating more appropriately and communicating more effectively within a diverse context, was employed. This is a process of cultural humility, as it involves a desire to learn from others. Cultural competence is a continuous process and not an event, which involves cultural awareness, cultural knowledge, cultural skills, cultural encounters and cultural desire. To gain cultural awareness, I performed an autoethnography, as well as an ethnographic analysis of South African history to discover the intellectual baggage transmitted to me from generation to generation. White supremacy, an ideology based on eurocentrism, a specific form of ethnocentrism, was found to have had a major influence in the cause and maintenance of oppressive inter-group relationships. With this knowledge, I conducted a self-redefinition to set standards for my future practice based on the internal cultural constructs of values, beliefs, attitudes, assumptions, norms and lifeways. Ultimately, I discovered that excellence in teaching practice, scholarship and leadership can be achieved by means of a teaching philosophy based on an ethic of caring. In other words, values stemming from a caring ethic steer practices towards being inclusive, appropriate and effective in relating to a diverse body of people within the context of higher education.

Hierdie "lewende" teorie is ontwikkel in reaksie op onweerlegbare getuienis dat rassisme en ander vorms van diskriminasie steeds by Suid-Afrikaanse universiteite beleef word. As wit vroulike opvoeder, het ek dit belangrik geag om my praktyke te ondersoek en te verseker dat ek sensitief is ten opsigte van die behoeftes van 'n diverse studentekorps. Met toewyding aan 'n proses van persoonlike transformasie, het ek "lewende" aksienavorsing toegepas om antwoorde te vind op die vraag: "Hoe transformeer ek my praktyke om meer insluitend, toepaslik en effektief te wees in verhoudinge met 'n diverse groepering van mense binne die konteks van hoër onderwys?" Ten einde intergroepverhoudinge beter te verstaan, het ek 'n uitgebreide konsepanalise onderneem deur veelvuldige perspektiewe vanuit die literatuur te bestudeer. Etnosentrisme, wat verskeie uitdrukkingsvorme behels, is as belangrikste struikelblok in interkulturele verhoudinge geïdentifiseer en gevolglik het ek my daarop toegelê om wyses te ondersoek waardeur etnosentrisme oorkom kon word. Kulturele bevoegdheid, 'n transformatiewe proses, wat 'n voortdurende strewe na toepaslike verhoudinge en effektiewe kommunikasie binne 'n diverse konteks behels, is toegepas. Dit is 'n proses van kulturele verootmoediging, aangesien dit spruit uit die begeerte om van ander te leer. Kulturele bevoegdheid het nie 'n eindbestemming nie, maar is 'n voortdurende proses wat kulturele bewuswording, kulturele kennis, kulturele vaardighede, kulturele ontmoetings en kulturele begeerte omvat. In die nastreef van kulturele bewuswording, het ek 'n outo-etnografie, asook 'n etnografiese analise van Suid-Afrikaanse geskiedenis onderneem, om vas te stel wat die intellektuele bagasie is wat van geslag tot geslag aan my oorgedra is. Ek het ontdek dat Wit-oppergesag, 'n ideologie wat op blanksentrisme, 'n spesifieke vorm van etnosentrisme, gebaseer is, "n beduidende invloed op die ontstaan en instandhouding van onderdrukkende intergroepverhoudinge gehad het. Met hierdie kennis as agtergrond, het ek 'n herdefiniëring van myself onderneem om nuwe standaarde vir my toekomstige praktyke te stel, wat op die interne kulturele konstrukte van waardes, geloof, gesindheid, aannames, norme en lewenswyse berus. Uiteindelik het ek ontdek dat uitnemendheid in onderrigpraktyk, leermeesterskap van onderrig/leer en onderrigleierskap bereik kan word deur middel van 'n onderrigfilosofie, wat op 'n etiek van omgee gebaseer is. Met ander woorde, dat waardes wat vanuit 'n etiek van omgee spruit, praktyke kan rig om meer insluitend, toepaslik en effektief te wees in verhoudinge met 'n diverse groepering van mense binne die konteks van hoër onderwys.
Thesis (Ph.D. (Higher Education Studies))--University of the Free State, 2011
Keywords: Multicultural education -- South Africa -- Free State; Cultural competence -- Study and teaching -- South Africa -- Free State; Educational change -- South Africa -- Free State; Race relations -- Study and teaching -- South Africa -- Free State